SPENDING PATTERNS ON MILLENNIAL GENERATION IN SURABAYA - Mariana Ing Malelak; Nathania Mirabel Halim (Finance and Investment Program, School of Business and Management - Petra Christian University, 2021)
This study aims to examine spending patterns in the millennial generation in Surabaya. Respondents of this study were the millennial generation who were divided into two age groups, namely 21-28 years old, who were referred to as junior millennials, and those aged 29-36 years who were referred to as senior millennials. The analysis technique used is a crosstab to examine the relationship between age and spending pattern of the millennial generation and an independent-sample t-test to test the difference between the spending pattern of the junior millennials and senior millennials. This study showed a significant relationship between age and spending pattern on the millennial generation, and there is a significant difference between the spending pattern of the junior millennials and senior millennials.